Prevalence and clinical significance of aortic valve prolapse. - Shapiro, L M (1985)
The prevalence and clinical significance of aortic valve prolapse were determined prospectively in 2000 consecutive patients undergoing routine clinical cross sectional echocardiography. Two hundred and twelve patients were excluded because the aortic cusps were not adequately visualised. Aortic valve prolapse was defined as downward displacement of cuspal material below a line joining the points of attachment of the aortic valve leaflets. Twenty four cases of aortic valve prolapse (1.2%) were identified. The patients were aged 12-64 years and nine were women. All had underlying valvar heart disease and the commonest lesion (in 11 cases) was prolapse of the larger cusp in bicuspid valves. Aortic valve prolapse was seen in four patients with mitral valve prolapse (two with severe regurgitation), one of whom had marfanoid aortic root dilatation. The remaining examples of aortic prolapse were seen in patients with various disorders including one with pulmonary atresia, two with aortic root disease (one with dissection and one with idiopathic dilatation), and one case of severe mitral regurgitation. Valves destroyed by infective endocarditis were seen in two cases. Aortic valve prolapse may be detected in various cardiac disorders and does not imply the presence of aortic regurgitation, but when bicuspid aortic valves are present it may well be important in producing such regurgitation. Although aortic valve prolapse may be associated with severe forms of mitral valve prolapse, these patients rarely have aortic regurgitation.